Ivermectin synergizes sorafenib in hepatocellular carcinoma via targeting multiple oncogenic pathways. Issue 3 (14th May 2022) - Lu, Haofeng; Zhou, Lin; Zuo, Hongping; Le, Wenjin; Hu, Jianfei; Zhang, Tiequan; Li, Mi; Yuan, Yufeng
Abstract: Advanced hepatocellular carcinoma (HCC) results in generally poor clinical outcomes and necessitates better therapeutic strategies. Ivermectin, which is an existing anti‐parasitic drug, has been recently identified as a novel anti‐cancer drug. In line with previous efforts, this work demonstrates the translational potential of ivermectin to treat advanced HCC. We demonstrated that ivermectin at clinically relevant concentrations was active against growth and survival in multiple HCC cell lines. We showed that ivermectin had the potential to inhibit metastasis and target HCC stem cell functions. Mechanism studies correlated well with cellular phenotypes observed in ivermectin‐treated cells, and demonstrated inhibition of mTOR/STAT3 pathway, suppression of epithelial mesenchymal transition (EMT) and reduced expression of stem cell markers. We further demonstrated that ivermectin inhibited tumor formation and growth in HCC xenograft mouse model, without causing significant toxicity in the mice. Using combination index (CI), we showed that ivermectin and sorafenib were synergistic in HCC in vitro, and this was further confirmed in vivo. Our work demonstrates the potent anti‐HCC activities of ivermectin and its multiple targets on essential oncogenic pathways. Our findings provide preclinical evidence to initialize clinical trial using ivermectin and sorafenib for treating advanced HCC. Abstract : Ivermectin inhibited biological activities of HCC cells and suppressed tumor formation and growth in HCC xenograft mouse model. Combination index analysis showed that ivermectin and sorafenib were synergistic in HCC in vitro, and this was further confirmed in vivo. Our work demonstrates the potent anti‐HCC activities of ivermectin and its multiple targets on essential oncogenic pathways.